Optimization of kidney function in cardiac surgery patients with intra-abdominal hypertension: expert opinion - Vanessa Moll; Ashish K. Khanna; Andrea Kurz; Jiapeng Huang; Marije Smit; Madhav Swaminathan; Steven Minear; K. Gage Parr; Amit Prabhakar; Manxu Zhao; Manu L. N. G. Malbrain (Perioperative Medicine, 2024)
Abstract Cardiac surgery-associated acute kidney injury (CSA-AKI) affects up to 42% of cardiac surgery patients. CSA-AKI is multifactorial, with low abdominal perfusion pressure often overlooked. Abdominal perfusion pressure is calculated as mean arterial pressure minus intra-abdominal pressure (IAP). IAH decreases cardiac output and compresses the renal vasculature and renal parenchyma. Recent studies have highlighted the frequent occurrence of IAH in cardiac surgery patients and have linked the role of low perfusion pressure to the occurrence of AKI. This review and expert opinion illustrate current evidence on the pathophysiology, diagnosis, and therapy of IAH and ACS in the context of AKI.